O DIAGNÓSTICO, O LAUDO CLÍNICO E A ESCOLARIZAÇÃO DOS ALUNOS PÚBLICO DA EDUCAÇÃO ESPECIAL - Will, Francilene dos Santos (2021)
This research aims at discussing both the utilization of clinical certificate in school and schooling challenges, considering the Specialized Educational Assistance for students who are public for Special Education, in the first school years of an elementary school in São Gabriel da Palha, ES, Brazil. Ethnographic-type case study underlies this qualitative research, with semi-structured interview, focus-group, and participant observation as data-collection instruments. Literature in the area indicates the utilization of diagnostic/clinical certificate in the school ambit, following the collective imaginary, becoming a barrier to schooling, and, consequently, to the apprenticeship and development of the student who is public for special education. Theoretical references are Mikhail Bakhtin, considering some aspects on speech analysis, and Lev Semenovich Vygotsky, with contributions under the historical-cultural perspective. Data produced and analyzed highlight the influence of diagnostic/clinical certification over pedagogical practices and schooling of students who are public for special education, as well as the need for actions, partnerships and participant ambiances, making collaboration and interaction between family and school also possible. We conclude that opening up a space for the reflection about the theme in the town is important to generate dialogues that neither reproduce excluding speeches nor excluding practices. The educational product has been developed out of the education professionals’ narratives, which made us understand the need for clarification around the utilization of diagnostic and clinical certificate to access schooling of and specialized educational assistance for students who are public for special education, being that a contribution to municipal education.